The geopolitical bet of the Russian invasion of Ukraine: a revival of realist theory and a new formation of the geopolitical map of the world. - Mallah, Hamid Mallah (Sharwes Scientific Journal, 2025)
The Russian-Ukrainian war is considered one of the most prominent geopolitical threats to European and global security. The war broke out in the context of Russia's fear of Ukraine's entry into the North Atlantic Treaty Organization (NATO) and its expansion into Central and Eastern Europe, and the West's efforts to contain Ukraine through Euro-Atlantic expansion and to encircle Russia geopolitically and geostrategically. Implementing Russia's famous advice. American strategic thinker Zbigniew Brzezinski says: If we want to get rid of...Russia, we have to separate from Ukraine.In the face of this situation and the threat it represents to its national and strategic security and the violation of its vital space, Russia seeks to defend itself, annex Ukraine to its geography, and restore the glories of the Soviet Union on the one hand, and not leave the matter to the West to exploit it as a trump card against it on the other hand.Based on the dimensions of the geopolitical stakes of the Russian invasion of Ukraine, we present readings and explanations for this invasion, which has moved from a crisis to a war and has become a serious threat to global security in its comprehensive sense.